1994
DOI: 10.1111/j.1471-0528.1994.tb13007.x
|View full text |Cite
|
Sign up to set email alerts
|

Charts of fetal size: 2. Head measurements*

Abstract: Objective To construct new size charts for fetal head circumference, biparietal diameter and other head dimensions. Design A prospective, cross sectional study. Setting The routine ultrasound department of a London teaching hospital. Subjects The fetuses of 663 women seen in the routine antenatal booking clinic whose ultrasound and menstrual dates agreed within 10 days. Methods Fetuses were scanned once only for the purpose of the study at gestations between 12 and 42 weeks, when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
297
6
9

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(325 citation statements)
references
References 9 publications
13
297
6
9
Order By: Relevance
“…The linear growth of BPD and HC until 34 weeks of pregnancy and the charts derived in this study for the 50th centiles of BPD and HC showed a close agreement with published charts from other countries and another Pakistani cohort [14,17,18]. Continuous linear growth of AC was seen from 16 weeks to the end of pregnancy.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The linear growth of BPD and HC until 34 weeks of pregnancy and the charts derived in this study for the 50th centiles of BPD and HC showed a close agreement with published charts from other countries and another Pakistani cohort [14,17,18]. Continuous linear growth of AC was seen from 16 weeks to the end of pregnancy.…”
Section: Discussionsupporting
confidence: 70%
“…While growth measurement centiles have been generated by various investigators using standard parameters [11][12][13][14][15][16], almost all fetal biometric growth centiles using sonographic anthropometric measurements have been derived from data from European and American populations [11][12][13][14][15]17]; only a few studies have used Asian women [16,18]. Fetal anthropometric data from the population in Pakistan are limited [18] and fetal centiles derived from other ethnic populations applied in our locality might lead to systematic errors in estimation.…”
Section: Introductionmentioning
confidence: 99%
“…In pregnancies less than 13 weeks and 6 days, we used crown-rump length and Robinson's chart 15 . Between 14 and 20 weeks, we used biparietal diameter and head circumference and the charts of Chitty 16 . Trained ultrasonographers at each of the two maternity hospitals of the Southeast Metropolitan Public Health Service performed the scans.…”
Section: Methodsmentioning
confidence: 99%
“…Ultrasound-derived gestational age assessment was used when menstrual dates were unknown (n = 310, 31%) or when measurement of fetal size fell more than 2 SD above or below the mean for gestation calculated from menstrual history (n = 220, 22%). Gestational age was calculated from the charts of Chitty et al 15,16 .…”
Section: Methodsmentioning
confidence: 99%